Prepositional clauses in Spanish : a diachronic and comparative syntactic study - Cantero, Manuel Delicado (Studies in Language Change SLC., 2013)
This book presents a historical and comparative syntactic analysis of Spanish prepositional clauses - traditionally called complement and adverbial clauses. This study examines the properties behind the evolution of clauses introduced by prepositions in Spanish, including clausal nominality, argumenthood, and preposition optionality. It devotes special attention to the nature and constraints of comparable constructions in other past and present European languages, particularly Portuguese, French, and Italian.